6(x-.8)-.2(5x-4)=3

Simple and best practice solution for 6(x-.8)-.2(5x-4)=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x-.8)-.2(5x-4)=3 equation:


Simplifying
6(x + -0.8) + -0.2(5x + -4) = 3

Reorder the terms:
6(-0.8 + x) + -0.2(5x + -4) = 3
(-0.8 * 6 + x * 6) + -0.2(5x + -4) = 3
(-4.8 + 6x) + -0.2(5x + -4) = 3

Reorder the terms:
-4.8 + 6x + -0.2(-4 + 5x) = 3
-4.8 + 6x + (-4 * -0.2 + 5x * -0.2) = 3
-4.8 + 6x + (0.8 + -1x) = 3

Reorder the terms:
-4.8 + 0.8 + 6x + -1x = 3

Combine like terms: -4.8 + 0.8 = -4
-4 + 6x + -1x = 3

Combine like terms: 6x + -1x = 5x
-4 + 5x = 3

Solving
-4 + 5x = 3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + 5x = 3 + 4

Combine like terms: -4 + 4 = 0
0 + 5x = 3 + 4
5x = 3 + 4

Combine like terms: 3 + 4 = 7
5x = 7

Divide each side by '5'.
x = 1.4

Simplifying
x = 1.4

See similar equations:

| -2(z+4)=-46 | | x^2+8x-272=0 | | -1/2(x+2)+3x=-1 | | 30=-5(6n+4)+5n | | 3/4×4 | | 7r+43=1 | | 25(x+7)=9x-2 | | -3=2y+35 | | (3/7)m=6 | | X-8=2+7x-5x | | P(x)=15x-125 | | 2x+x=11+3-4x | | s+3t=-4 | | 75-u=272 | | 21x^2-76x+20=0 | | 12x+18=56-7x | | 1/5x-5/6=3/4x-5 | | 2z+x=8z-12 | | 2-2x=-7x | | 12+4z=8(z-1) | | -5b= | | x^2=100-2x^2 | | -8g+6=30 | | 15x^2=8x-16 | | -68=-5x-6x+9 | | 4x-1/2=10 | | 18x+18-47x=255 | | 3x-5x-40= | | 4x-2+6=7x-3 | | 3x+y=w | | 5x+5+25=0 | | -3h=3h-7 |

Equations solver categories